Larval morphology of the Neotropical diving beetle genus Hemibidessus Zimmermann, 1921 (Coleoptera: Dytiscidae: Bidessini) - Michat, Mariano C.; Alarie, Yves; Benetti, Cesar J. (Zootaxa, 2022)
We describe for the first time the larva of the diving-beetle genus Hemibidessus Zimmermann, 1921, based on instars II and III of H. conicus (Zimmermann, 1921). We include detailed morphometric and chaetotaxic analyses of the cephalic capsule, head appendages, legs, last abdominal segment and urogomphi in order to discover useful characters for distinguishing Hemibidessus larvae from those of other known Bidessini. Hemibidessus larvae characteristically have elongate legs armed with natatory setae and elongate urogomphi that bear numerous secondary setae, features commonly associated with an increased swimming ability. These characters are shared with Brachyvatus Zimmermann, 1921, suggesting a close phylogenetic relationship between these two genera. The primary seta UR8 is inserted apically on urogomphomere 2 in Hemibidessus larvae, a feature so far only shared with the mature larva of Yola Gozis, 1886. Other characters that combined with those previously mentioned are useful to distinguish Hemibidessus from other bidessines are the absence of a ventroapical spinula on antennomere 3 and the presence of secondary dorsal setae on protarsus.